2017
DOI: 10.1080/10962247.2017.1334718
|View full text |Cite
|
Sign up to set email alerts
|

Novel hybrid composite discharge electrode for electrostatic precipitator

Abstract: The newly invented hybrid composite electrode (HCE) performance was evaluated through experimentation with conventional metal electrodes. The HCE performance was comparable to the metal electrodes. The HCE also exhibited uniform corona fields and steady power while maintaining similar and in some cases superior electrical performance as compared with metal electrodes and thus shows a significant potential to substitute metal electrodes in wet ESP systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…13,20 Numerous studies on the discharge characteristics of wire-plate ESPs have been reported; these studies include investigations of emitter geometry and material on the electrode corona discharge to optimize the discharge electrode through experimental and numerical methods. [21][22][23][24][25] Electrodes with different shapes, diameters, and intervals were tested in an experimental-scale ESP at high temperatures, 26,27 and migration velocity was also investigated. 28,29 Corona discharge and particle collection characteristics in a wet ESP with a ne water mist were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…13,20 Numerous studies on the discharge characteristics of wire-plate ESPs have been reported; these studies include investigations of emitter geometry and material on the electrode corona discharge to optimize the discharge electrode through experimental and numerical methods. [21][22][23][24][25] Electrodes with different shapes, diameters, and intervals were tested in an experimental-scale ESP at high temperatures, 26,27 and migration velocity was also investigated. 28,29 Corona discharge and particle collection characteristics in a wet ESP with a ne water mist were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Although composite discharge electrodes in the previous studies had shown tremendous potential, the structural stiffness of the composite discharge electrodes, especially at large/commercial scale, presented challenges under the gas flow as even a small amount of discharge electrode vibration could potentially cause excessive sparking. To address these issues, a novel hybrid composite electrode (HCE) was developed earlier, with patent pending (Alam and Ali 2018), that combined the complementary properties of a metal and carbon fiber (Ali et al 2017). The HCE provided excellent stiffness and abrasion and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…e relevant study on an electrostatic precipitator is mainly focused on the dusting principle or filtration characteristics [9,10], the collection efficiency or dusting method [11][12][13], the collected dust or the particulate matter [14,15], the analysis of the operating [16,17], and the electrode system or recovery system [18][19][20] but ignored the study of its bearing structure [21,22]. e main frame structure is often designed and transformed by companies with analogy method and empirical design instead of precise and scientific calculation.…”
Section: Introductionmentioning
confidence: 99%